2016
DOI: 10.7554/elife.14620
|View full text |Cite
|
Sign up to set email alerts
|

A long non-coding RNA targets microRNA miR-34a to regulate colon cancer stem cell asymmetric division

Abstract: The roles of long non-coding RNAs (lncRNAs) in regulating cancer and stem cells are being increasingly appreciated. Its diverse mechanisms provide the regulatory network with a bigger repertoire to increase complexity. Here we report a novel LncRNA, Lnc34a, that is enriched in colon cancer stem cells (CCSCs) and initiates asymmetric division by directly targeting the microRNA miR-34a to cause its spatial imbalance. Lnc34a recruits Dnmt3a via PHB2 and HDAC1 to methylate and deacetylate the miR-34a promoter simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 51 publications
(59 reference statements)
5
88
0
Order By: Relevance
“…Hence, lncRNAs may play an important role in tumorigenesis and tumour progression [23]. Numerous studies have confirmed that lncRNAs are involved in the tumorigenesis and development of CRC via multiple pathways, such as DNA methylation and histone modifications [24, 25]. These findings have posed the question of how to accurately screen for lncRNAs of interest within the vast amount of data already available.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, lncRNAs may play an important role in tumorigenesis and tumour progression [23]. Numerous studies have confirmed that lncRNAs are involved in the tumorigenesis and development of CRC via multiple pathways, such as DNA methylation and histone modifications [24, 25]. These findings have posed the question of how to accurately screen for lncRNAs of interest within the vast amount of data already available.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA34a recruits DNMT3a to establish de novo DNA methylation, and histone deacetylase 1 (HDAC1) to deacetylate and methylate the miRNA34a promoter, in a manner reminiscent of protein‐mediated DNA methylation. Ultimately, this process regulates asymmetric colorectal cancer stem cell division . Another miRNA, miRNA‐146a , targets NUMB to stabilize β‐CATENIN, controlling cell division of colorectal cancer stem cells .…”
Section: Epigenetic Regulation Of Crypt Cell Maintenance and Differenmentioning
confidence: 99%
“…The results of clinical features showed that TUSC7 was associated with tumor size, HOTAIR with tumor size and TNM-stage. In table 1, we concluded a correlation with CRC clinical features and lncRNAs for visually understanding that lncRNAs might be as markers for CRC diagnosis (Table 1) [16, 17, 47, 57, 75-80]. Sun et al reported that ANRIL could enhance cell mobility and invasion by in-vitro tube formation HLECs invasion.…”
Section: Clinical Significance Of Lncrnas For Crcmentioning
confidence: 99%
“…Recently, Lihua et al found a novel lncRNAs, lnc34a, was notably upregulated in colon cancer stem cell (CCSC) lines and promoted CCSC self-renewing and tumorigenesis. Moreover, lnc34a recruit Dnmt3a via PHB2 and HDAC1 to target miR-34a by methylating and deacetylatingits promoter to promote CRC cell proliferation [47]. Upregulated GAS5 reduced ability of cell proliferation, and promoted G0/G1 cell cycle arrest and apoptosis [48].…”
Section: The Role Of Lncrnas In Crcmentioning
confidence: 99%